The role of Sodium Benzoate in controlling corrosion of stainless steel in seawater environment - S. Y., Seoh; Mohammed Misbahul, Amin; H. B., Senin (University College of Science and Technology Malaysia, 2009)
The controlling corrosion of stainless steel has been investigated under the sea water environment. The aim of this study is to prevent the stainless steel from corrosion by using sodium benzoate as inhibitor. Three set of samples have been prepared where sodium benzoate have been added with molarities of 0.3M, 0.6M and 1.0M respectively. Besides this, one set of sample has been done without adding sodium benzoate. This is to enable a comparison of the inhibited environment's rate of corrosion to be made. As no inhibitor was added to the seawater, the highest corrosion rate was observed for this stainless steel. As increasing the concentration of sodium benzoate, it decreases the corrosion rate. Results also show that by the addition of 1.0M of sodium benzoate in seawater samples, it giving the very high efficiencies (> 90%).